Pendugaan umur simpan coklat instan kemasan plastik polipropilen menggunakan pendekatan model Arrhenius [Shelf life prediction of instant chocolate in poly propylene (PP) plastic packaging using Arrhenius model approach] - Hidayati, Sri; Sartika, Dewi; Suharyono, Suharyono; Sutoyo, Sutoyo (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
The research aimed to predict instant chocolate's shelf life using the Accelerated Shelf Life Test (ASLT) method with the Arrhenius equation. Instant chocolate was stored at 30oC, 40oC, and 50oC in polypropylene plastic packaging for 42 days and observed changes in water content, free fatty acids, and aroma. The results showed an increase in temperature and storage time resulted in an increase in moisture and FFA content but decreased the aroma score of instant chocolate stored using polypropylene packaging. Shelf life estimates were based on free fatty acids and first-order reactions. The shelf life of instant chocolate stored at 30oC Â was 214 days, at 40oC was 140.79 days, and at 50oC condition was 113 days. Â